Real Option-Based decision model for fuel saving devices in transportation vehicles under flexible design. Issue 1 (2nd January 2022) - Min, K. Jo; Jackman, John
Abstract: Operations that depend on transportation vehicles experience a high degree of uncertainty in fuel costs. We construct and analyze the engineering economic problem of how to value flexibility when the vehicle design under consideration enables fuel savings in the future by incurring an initial cost for the vehicle to incorporate features that will support future modifications. For a vehicle manufacturer working with a customer, we derive the optimal threshold fuel costs to incorporate such features and to decommission under the net benefit maximization through a real options approach. From these derivations as well as an illustrative example in the case of winglets for aircraft, we present the managerial insights and economic implications of the flexible design in transportation vehicles.